Year-round measurements of size-segregated low molecular weight organic acids in Arctic aerosol - Feltracco M.; Barbaro E.; Spolaor A.; Vecchiato M.; Callegaro A.; Burgay F.; Varde M.; Maffezzoli N.; Dallo F.; Scoto F.; Zangrando R.; Barbante C.; et al. (Science of The Total Environment, 2021)
Organic acids in aerosols Earth's atmosphere are ubiquitous and they have been extensively studied across urban, rural and polar environments. However, little is known about their properties, transport, source and seasonal variations in the Svalbard Archipelago. Here, we present the annual trend of organic acids in the aerosol collected at Ny-Ålesund and consider their size-distributions to infer their possible sources and relative contributions. A series of carboxylic acids were detected with a predominance of C2-oxalic acid. Pinic acid and cis-pinonic acid were studied in order to better understand the oxidative and gas-to-particle processes occurred in the Arctic atmosphere. Since the water-soluble organic fraction is mainly composed by organic acids and ions, we investigated how the seasonal variation leads to different atmospheric transport mechanisms, focusing on the chemical variations between the polar night and boreal summer. Using major ions, levoglucosan and MSA, the Positive Matrix Factorization (PMF) identified five different possible sources: a) sea spray; b) marine primary production; c) biomass burning; d) sea ice related process and e) secondary products.